Hubungan Terpaan Iklan Program Magang Kampus Merdeka di Instagram dengan Minay Viewer’s Mengikuti Program Magang Kampus Merdeka - Nabila Saptariani Shafira; Dede Lilis Chaerowati (Bandung Conference Series: Communication Management, 2022)
Abstract. This internship is an important requirement in completing the educational process at universities or colleges, especially students who are in their final semester. Internship programs are carried out in the world of work, which are useful for providing experience and knowledge and forming professional skills. One of them, independent campuses make internship and study programs. certified independent (MSIB). The purpose of this study is to find out there is a relationship between frequency, intensity, duration on Instagram @kampusmerdak.ri with attention, desire, and studying viewers to take part in the independent campus internship program. The theoretical basis used is the Advertising Exposure theory. The research method used is correlational quantitative. Data analysis techniques using questionnaires, observations and literature. The results of this study showed that the entire hypothesis that was tested got Ho rejected, which means that there is a relationship between frequency, intensity and duration on Instagram @kampusmerdeka.ri with attention, desire, learning to take part in the independent campus internship program. Abstrak. Magang ini sebagai persyaratan penting dalam menyelesaikan proses pendidikan di universitas atau perguruan tinggi khususnya mahasiswa yang sedang di semester akhir, Program magang dilaksanakan dalam dunia kerja berguna untuk memberikan bekal pengalaman dan ilmu dan membentuk keahlian secara profesional Salah satunya, kampus merdeka membuat program magang dan studi independen bersertifikat (MSIB). Tujuan penelitian ini untuk mengetahui terdapat hubungan antara frekuensi, intensitas, durasi di instagram @kampusmerdak.ri dengan perhatian, keinginan, mempelajari viewers untuk mengikuti program magang kampus merdeka. Landasan teori yang digunakan adalah teori Advertising Exposure. Metode penelitian yang digunakan kuantitatif korelasional. Teknik analisis data menggunakan kuesioner, observasi dan kepustakaan. Hasil dari penelitian ini keseluruhan hipotesis yang uji mendapatkan hasil Ho ditolak yang berarti bahwa terdapat hubungan antara frekuensi, intensitas dan durasi di instagram @kampusmerdeka.ri dengan perhatian, keinginan, mempelajari untuk mengikuti program magang kampus merdeka.